Building distinctive brand assets - Romaniuk, Jenni (Ascent Audio, 2023)
Building Distinctive Brand Assets is for anyone with a brand logo, font, or color scheme, and is essential listening for those who have wondered if (or have been told) it's time for a change. Listeners will learn how to set up a long-term strategy to build a strong brand identity, and how to make use of knowledge, metrics, and management systems in order to build and protect a brand's Distinctive Assets. Building Distinctive Brand Assets is divided into three sections that capture the processes involved in brand asset creation, implementation, and ongoing management. The first section is focuses on strategy, and covers how Distinctive Assets are created and their role in a broader brand equity building. The second section covers measurement approaches, and how to use and interpret key metrics. The third section delves into the strengths and weaknesses of different types of assets and introduces the idea of a Distinctive Asset palette. This section also outlines how to set up a Distinctive Asset management system to provide an early warning system to identify potential threats before they evolve into major issues.